PAOX1 expression in mixed-substrate continuous cultures of Komagataella phaffii (Pichia pastoris) is completely determined by methanol consumption regardless of the secondary carbon source - Singh, Anamika; Narang, Atul (Frontiers in Bioengineering and Biotechnology, 2023)
The expression of recombinant proteins by the AOX1 promoter of Komagataella phaffii is typically induced by adding methanol to the cultivation medium. Since growth on methanol imposes a high oxygen demand, the medium is often supplemented with an additional secondary carbon source which serves to reduce the consumption of methanol, and hence, oxygen. Early research recommended the use of glycerol as the secondary carbon source, but more recent studies recommend the use of sorbitol because glycerol represses PAOX1 expression. To assess the validity of this recommendation, we measured the steady state concentrations of biomass, residual methanol, and LacZ expressed from PAOX1 over a wide range of dilution rates (0.02–0.20 h−1) in continuous cultures of the Mut+ strain fed with methanol + glycerol (repressing) and methanol + sorbitol (non-repressing). We find that under these conditions, the specific PAOX1 expression rate (measured as either specific LacZ productivity or specific AOX productivity) is completely determined by the specific methanol consumption rate regardless of the type (repressing/non-repressing) of the secondary carbon source. In both cultures, the specific PAOX1 expression rate is proportional to the specific methanol consumption rate, provided that the latter is below 0.15 g/(gdw-h); beyond this threshold consumption rate, the specific PAOX1 expression rate of both cultures saturates to the same value. Analysis of the data in the literature shows that the same phenomenon also occurs in continuous cultures of Escherichia coli fed with mixtures of lactose plus repressing/non-repressing carbon sources. The specific Plac expression rate is completely determined by the specific lactose consumption rate, regardless of the type of secondary carbon source, glycerol or glucose.